2012
DOI: 10.1016/j.jplph.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of apoplastic and symplastic antioxidant system in shallot leaves: Impacts of weak static electric and magnetic field

Abstract: a b s t r a c tImpacts of electric and magnetic fields (EFs and MFs) on a biological organism vary depending on their application style, time, and intensities. High intensity MF and EF have destructive effects on plants. However, at low intensities, these phenomena are of special interest because of the complexity of plant responses. This study reports the effects of continuous, low-intensity static MF (7 mT) and EF (20 kV/m) on growth and antioxidant status of shallot (Allium ascalonicum L.) leaves, and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 42 publications
1
28
1
2
Order By: Relevance
“…These results suggested that apoplastic constituents may work as potentially important redox regulators sensing and signaling MF changes. Static continuous MF and EF at low intensities have distinct impacts on the antioxidant system in plant leaves, and weak MF is involved in antioxidant-mediated reactions in the apoplast, resulting in overcoming a possible redox imbalance (Cakmak et al, 2012). In mung bean seedlings treated with 600 mT MF followed by cadmium stress the concentration of malondialdehyde, H 2 O 2 and O − 2 , and the conductivity of electrolyte leakage decreased, while the NO concentration and NOS activity increased compared to cadmium stress alone, showing that MF compensates for the toxicological effects of cadmium exposure are related to NO signal (Chen et al, 2011).…”
Section: Exposure Of Plants To Mf Intensities Higher Than the Geomagnmentioning
confidence: 99%
“…These results suggested that apoplastic constituents may work as potentially important redox regulators sensing and signaling MF changes. Static continuous MF and EF at low intensities have distinct impacts on the antioxidant system in plant leaves, and weak MF is involved in antioxidant-mediated reactions in the apoplast, resulting in overcoming a possible redox imbalance (Cakmak et al, 2012). In mung bean seedlings treated with 600 mT MF followed by cadmium stress the concentration of malondialdehyde, H 2 O 2 and O − 2 , and the conductivity of electrolyte leakage decreased, while the NO concentration and NOS activity increased compared to cadmium stress alone, showing that MF compensates for the toxicological effects of cadmium exposure are related to NO signal (Chen et al, 2011).…”
Section: Exposure Of Plants To Mf Intensities Higher Than the Geomagnmentioning
confidence: 99%
“…All SODs are multimeric metallo proteins, very efficient at scavenging free radical [Scandalios, ]. It has been reported that SMFs increased lipid peroxidation, H 2 O 2 levels, and antioxidant enzyme activities including SOD in Allium ascalonicum L. leaves [Cakmak et al, ]. Increased SOD activities were also found in liver, kidney, muscle, and brain tissues of SMF exposed rats [Ghodbane et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using oscillating magnetic fields have uncovered new effects in the living systems of growth [12]. AMFs are also capable of changing a plant's growth rates [13], so their action on various biological systems can be used as effectively as a means of regulating the biological activity of plants and fruits [14]. For example, in the previous study, magnetic fields of different intensities had varying influences on the biology of PC12 cells [15].…”
Section: Introductionmentioning
confidence: 92%